A kind of thermal conductive silicone grease and its preparation method and application
By covering the surface of the alumina powder with acenaeta asphalt and achieving uniform dispersion in silicone oil, the problem of filler settlement in thermally conductive silicone grease is solved, and the thermal conductivity and service life are improved.
Patent Information
- Application Number
- CN202411968168.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
After long-term use of existing thermally conductive silicone grease, the filler is prone to settle, resulting in precipitation and volatility of silicone oil, affecting thermal conductivity and service life.
By covering the surface of the alumina powder with acenae asphalt and making the alumina powder have good compatibility with silicone oil through a specific preparation method, the uniform dispersion of the alumina powder in silicone oil is achieved.
The high thermal conductivity, uniformity and high temperature stability of thermal grease are achieved, extending service life and avoiding performance degradation caused by filler settlement.
Smart Images

Figure CN119775636A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal conductive silicone grease, in particular to a thermal conductive silicone grease with high dispersion and high thermal conductivity and an application of a preparation method thereof. Background Art
[0002] Thermal grease, commonly known as heat dissipation paste, is commonly used for heat conduction and heat dissipation of electronic components such as transistors, electron tubes, and CPUs. Filling the gap between components and heat sinks with thermal grease can ensure close contact between components and heat sinks, increase the contact area, improve heat transfer efficiency, and quickly and evenly spread the heat generated in the component studio to the heat sink, and finally take it away through the fan, thereby optimizing the heat dissipation efficiency.
[0003] Thermal grease is mainly made of silicone oil and thermal conductive filler. If the compatibility between the two materials is poor, the thermal grease will become drier and powdery under long-term operation, especially high-temperature operation, which will affect the service life of the thermal grease. In addition, the density of thermal grease is usually lower than the density of the filler. After long-term use, the filler will settle, causing the silicone oil in the thermal grease to precipitate and volatilize.
[0004] The Chinese patent application with publication number CN116254000A provides a thermally conductive silicone grease, which includes: silicone oil, thermally conductive filler, and fluorine-containing silane coupling agent. By introducing the fluorine-containing silane coupling agent, the fluorine-containing silane coupling agent can react chemically with the thermally conductive filler through hydrolysis to form hydroxyl groups, and has good compatibility with silicone oil, so it can serve as a bridge connecting the thermally conductive filler and silicone oil, thereby improving the structural stability of the thermally conductive silicone grease; and the introduction of fluorine atoms can make the thermally conductive silicone grease exhibit a lower dielectric constant; at the same time, the self-lubricating effect brought by the fluorine atoms can effectively inhibit the agglomeration of the thermally conductive filler, so that the thermally conductive silicone grease of the embodiment of the present application can have the advantages of excellent thermal conductivity, low dielectric constant and high reliability.
[0005] The Chinese patent application with publication number CN109370227A provides a new type of thermal conductive silicone grease. By modifying graphene, the self-lubricating property of thin-layer graphene is enhanced to avoid accumulation. As a dispersant for dispersing thermal conductive particles, the thermal conductive particles are evenly dispersed in the entire system, and the heat dissipation performance of the system is improved. Since the self-lubricating property of graphene is used as a dispersant instead of its thermal properties as a thermal conductive filler, the amount of addition is also reduced, which reduces costs on the one hand and avoids the viscosity of the composite material from increasing and the performance deteriorating on the other hand. Since the thermal conductive silicone grease has high thermal conductivity, the size of the radiator can be further shortened, and the size of the radiator is reduced to 4 / 5-5 / 6 of the original size.
[0006] However, none of the above prior arts solves the technical problem that the filler may settle after long-term use. Summary of the invention
[0007] The first object of the present invention is to provide an alumina powder having good compatibility with silicone oil.
[0008] The second object of the present invention is to provide a method for preparing the alumina powder.
[0009] The third object of the present invention is to provide a thermally conductive silicone grease comprising the alumina powder.
[0010] A fourth object of the present invention is to provide an application of thermally conductive silicone grease.
[0011] The present invention is achieved through the following technical solutions: An alumina powder, characterized in that: The surface of the aluminum oxide powder is coated with acenaphthylene oxide pitch.
[0012] The D50 of the alumina powder is 5-50 microns.
[0013] The method for preparing the alumina powder comprises the following steps: After mixing the aluminum oxide powder and acenaphthylene, heating is performed for the first time to polymerize the acenaphthylene, thereby obtaining an aluminum oxide powder with polyacenaphthylene coated on the surface; Plasma treatment is performed on the aluminum oxide powder with polyacenaphthylene coated on the surface to oxidize the polyacenaphthylene, thereby obtaining the aluminum oxide powder with polyacenaphthylene oxide coated on the surface; The aluminum oxide powder coated with oxidized polyacenaphthylene on the surface is heated for the second time to convert the oxidized polyacenaphthylene into acenaphthylene pitch.
[0014] The mass ratio of the aluminum oxide powder to acenaphthylene is 500-600:1.
[0015] The temperature of the first heating is 225-275°C.
[0016] The plasma treatment time is 5-10min; The gas used in the plasma treatment includes nitrogen or argon; The plasma source power used in the plasma treatment is 400-500W.
[0017] The temperature of the second heating is 400-500°C.
[0018] A thermally conductive silicone grease comprises the alumina powder.
[0019] The thermal conductive silicone grease comprises 15-20 parts of silicone oil, 50-80 parts of alumina powder, and 1-3 parts of silica gel by weight; The silicone oil includes dimethyl silicone oil or methyl silicone oil.
[0020] An application of thermal conductive silicone grease is used for heat dissipation of electronic components.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The surface of the aluminum oxide powder provided by the present invention is coated with acenaphthylene oxide pitch, and the acenaphthylene oxide pitch is a pitch mainly composed of decacyclic ene, which has a very good affinity with silicone oil and can be evenly dispersed in the silicone oil. Because it can be evenly dispersed in silicone oil, the aluminum oxide powder is used to prepare thermally conductive silicone oil, and a thermally conductive silicone grease with uniform heat dissipation can be obtained.
[0022] The preparation method of the alumina powder provided by the invention is simple and can be produced industrially.
[0023] The thermally conductive silicone grease provided by the invention has high thermal conductivity, good uniformity and high high-temperature stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The SEM photograph of the thermal conductive silicone grease prepared in Example 4 is shown.
[0025] Figure 2 The SEM photograph of the thermal conductive silicone grease prepared in Example 4 is shown.
[0026] Figure 3 The SEM photograph of the thermal conductive silicone grease prepared in Comparative Example 1 is shown. DETAILED DESCRIPTION
[0027] The present invention provides an aluminum oxide powder, the surface of which is coated with acenaphthylene oxide pitch. Since the acenaphthylene oxide pitch is rich in hydroxyl and carboxyl groups, it has high affinity with the aluminum oxide powder and strong binding force. At the same time, the pitch is rich in decacyclic olefins, so it has high affinity for silicone oil. Preferably, when the D50 of the alumina powder is 5-50 microns, its dispersibility in silicone oil is optimal.
[0028] The present invention also provides a method for preparing the alumina powder, which specifically comprises the following steps: After the alumina powder and acenaphthylene are mixed, they are heated for the first time to polymerize acenaphthylene to obtain alumina powder coated with polyacenaphthylene on the surface; the alumina powder coated with polyacenaphthylene on the surface is treated with plasma to oxidize polyacenaphthylene to obtain alumina powder coated with oxidized polyacenaphthylene on the surface; after polyacenaphthylene is oxidized, hydroxyl and carboxyl groups are connected, which increases the affinity of polyacenaphthylene with alumina, so that polyacenaphthylene is stably coated on the surface of alumina powder. In addition, hydroxyl and carboxyl groups can also provide electrostatic repulsion to improve the dispersibility of alumina powder. Then, the alumina powder coated with oxidized polyacenaphthylene on the surface is heated for the second time to convert oxidized polyacenaphthylene into acenaphthylene pitch, thereby increasing the affinity of alumina for silicone oil and making it evenly dispersed in silicone oil. Silica gel can increase the viscosity of thermal grease. Silica gel can also slow down the drying speed of thermal grease. Silicone oil is the base oil of the thermally conductive silicone grease, and the thermally conductive filler material added therein can significantly enhance the thermal conductivity and durability of the thermally conductive silicone grease.
[0029] Preferably, the mass ratio of the aluminum oxide powder to acenaphthylene is 500-600: 1. Too thick an acenaphthylene coating layer will reduce the thermal conductivity of the aluminum oxide powder.
[0030] Preferably, the temperature of the first heating is 220-270° C. At this temperature, acenaphthylene will self-polymerize to obtain polyacenaphthylene.
[0031] Preferably, the plasma treatment time is 5-10 min; the gas used in the plasma treatment includes nitrogen or argon; the plasma source power used in the plasma treatment is 400-500W.
[0032] The temperature of the second heating is 400-500° C. At this temperature, the oxidized polyacenaphthylene can be converted into oxidized polyacenaphthylene asphalt.
[0033] The present invention also provides a thermal conductive silicone grease comprising the alumina powder. The alumina powder in the thermal conductive silicone grease is evenly dispersed and has good thermal conductivity.
[0034] Specifically, the thermal conductive silicone grease contains 15-20 parts of silicone oil, 50-80 parts of alumina powder, and 1-3 parts of silica gel by weight; specifically, the silicone oil can be dimethyl silicone oil and / or methyl silicone oil. Dimethyl silicone oil is the base oil of the thermal conductive silicone grease, and the thermal conductive filler material added therein can significantly enhance the thermal conductivity and durability of the thermal conductive silicone grease.
[0035] The microscopic molecular form of silica gel is a mesh. Alumina powder is mixed with silica gel, and continuously stirred and ground. During the grinding process, the alumina powder cuts off the molecular chain in the middle of the mesh silica gel, which reduces the molecular cross-linking degree in the silica gel, even if the viscosity of the silica gel is reduced, thereby reducing the effect of the addition of silica gel on the viscosity of the thermal grease. After the silica gel is ground with calcium carbonate powder, polyvinyl alcohol, hexamethyldisiloxane, tetraethyl silicate, ethyl subsilicate, tetraethoxysilane and other substances are added thereto. After these substances are fully mixed with the silica gel, dimethyl silicone oil, methyl silicone oil and other substances are added thereto. The silica gel is allowed to stand and foam, and is evenly mixed with other substances to form a uniform mixed dispersion. After that, a vacuum degassing treatment is performed to expand the volume of the mixed dispersion and remove the bubbles therein. Then, coupling agents, thermal conductive fillers, additives and other substances are added thereto and stirred evenly, thereby completing the preparation of the thermal grease. At the same time, decacyclic ene may also enter the silica gel during the grinding process, improving the compatibility of silica gel and alumina and preventing alumina from agglomerating.
[0036] The thermally conductive silicone grease has excellent thermal conductivity and can be used for heat dissipation of electronic components.
[0037] An application of thermal grease is used for heat dissipation of electronic components. Since the thermal grease has low viscosity and good fluidity, when the heat sink is attached with force, the thermal grease completely fits the shapes of the two opposite sides of the heat sink and the electronic components, thereby avoiding the reduction of the heat dissipation effect caused by the presence of pores between the heat sink and the electronic components. When using thermal grease, a surface coating method is usually adopted, that is, a thick layer of thermal grease is coated on the surface of the electronic component, and then the heat sink is adhered thereto. When using the thermal grease in this solution, it is only necessary to evenly drip the thermal grease on the electronic components, thereby reducing the amount of thermal grease used.
[0038] The present invention is further described below with reference to specific embodiments. Preparation of thermal conductive fillers Alumina powder with an average particle size of 25 microns was mixed with acenaphthylene (purchased from Sigma-Aldrich CAS No.: 208-96-8) at a weight ratio of 500:1, and then heated to 250°C to polymerize acenaphthylene to obtain alumina powder with polyacenaphthylene coated on the surface; The aluminum oxide powder coated with polyacenaphthylene on the surface is placed in a plasma generator for plasma treatment, the treatment power is 450W, the treatment time is 10 minutes, the treatment gas is a mixed gas of nitrogen and oxygen, wherein the volume ratio of nitrogen to oxygen is 95:5. The plasma oxidizes the polyacenaphthylene to obtain an aluminum oxide powder coated with oxidized polyacenaphthylene on the surface; The alumina powder coated with oxidized polyacenaphthylene is heated for the second time to 500° C. to convert the oxidized polyacenaphthylene into acenaphthylene pitch.
[0039] Example 2 Preparation of thermal conductive fillers Alumina powder with an average particle size of 35 microns and acenaphthylene (purchased from Sigma-Aldrich CAS No.: 208-96-8) were mixed at a weight ratio of 550:1, and then heated to 250°C to polymerize acenaphthylene to obtain alumina powder with polyacenaphthylene coated on the surface; The aluminum oxide powder coated with polyacenaphthylene on the surface is placed in a plasma generator for plasma treatment, the treatment power is 450W, the treatment time is 10 minutes, and the treatment gas is a mixed gas of nitrogen and oxygen, wherein the volume ratio of nitrogen to oxygen is 93:7. The plasma oxidizes the polyacenaphthylene to obtain aluminum oxide powder coated with oxidized polyacenaphthylene on the surface; The alumina powder coated with oxidized polyacenaphthylene is heated for the second time to 550° C. to convert the oxidized polyacenaphthylene into acenaphthylene pitch.
[0040] Example 3 Preparation of thermal conductive fillers Alumina powder with an average particle size of 50 microns was mixed with acenaphthylene (purchased from Sigma-Aldrich CAS No.: 208-96-8) at a weight ratio of 600:1, and then heated to 270°C to polymerize acenaphthylene to obtain alumina powder with polyacenaphthylene coated on the surface; The aluminum oxide powder coated with polyacenaphthylene on the surface is placed in a plasma generator for plasma treatment, the treatment power is 500W, the treatment time is 6 minutes, and the treatment gas is a mixed gas of nitrogen and oxygen, wherein the volume ratio of nitrogen to oxygen is 90:10. The plasma oxidizes the polyacenaphthylene to obtain an aluminum oxide powder coated with oxidized polyacenaphthylene on the surface; The alumina powder coated with oxidized polyacenaphthylene is heated for the second time to 550° C. to convert the oxidized polyacenaphthylene into acenaphthylene pitch.
[0041] Example 4 15 g of calcium carbonate powder with an average particle size of 0.3 μm was added to 100 g of silica gel and ground and stirred for 2 hours, and then 1500 g of dimethyl silicone oil was added and stirred continuously. Then, vacuum degassing was performed at 35° C., and then 5000 g of the thermal conductive filler prepared in Example 1 was added and stirred continuously. Finally, a second vacuum degassing treatment was performed.
[0042] Comparative Example 1 15g of calcium carbonate powder with an average particle size of 0.3μm was added to 100g of silica gel and ground and stirred for 2 hours, and then 500g of dimethyl silicone oil was added and stirred continuously. Then vacuum degassing was performed at 35°C, and then 5000g of alumina powder with an average particle size of 25 microns was added and stirred continuously. Finally, a second vacuum degassing treatment was performed.
[0043] Example 5 45 g of calcium carbonate powder with an average particle size of 0.3 μm was added to 300 g of silica gel and ground and stirred for 2 hours, and then 1500 g of dimethyl silicone oil was added and stirred continuously. Then, vacuum degassing was performed at 45° C., and then 5000 g of the thermal conductive filler prepared in Example 2 was added and stirred continuously. Finally, a second vacuum degassing treatment was performed.
[0044] Example 6 15 g of calcium carbonate powder with an average particle size of 0.3 μm was added to 100 g of silica gel and ground and stirred for 2 hours, and then 1500 g of dimethyl silicone oil was added and stirred continuously. Then, vacuum degassing was performed at 35° C., and then 5000 g of the thermal conductive filler prepared in Example 3 was added and stirred continuously. Finally, a second vacuum degassing treatment was performed.
[0045] Example 7 20 g of calcium carbonate powder with an average particle size of 0.3 μm was added to 100 g of silica gel and ground and stirred for 2 hours, and then 2000 g of dimethyl silicone oil was added and stirred continuously. Then, vacuum degassing was performed at 35° C., and then 8000 g of the thermal conductive filler prepared in Example 3 was added and stirred continuously. Finally, a second vacuum degassing treatment was performed.
[0046] Example 8 15 g of calcium carbonate powder with an average particle size of 0.6 μm was added to 150 g of silica gel and ground and stirred for 2 hours, and then 2000 g of dimethyl silicone oil was added and stirred continuously. Then, vacuum degassing was performed at 35° C., and then 6000 g of the thermal conductive filler prepared in Example 1 was added and stirred continuously. Finally, a second vacuum degassing treatment was performed.
[0047] Example 9 10g of calcium carbonate powder with an average particle size of 0.6μm was added to 300g of silica gel and ground and stirred for 2 hours, and then 1000g of dimethyl silicone oil and 500g of methyl silicone oil were added and stirred continuously. Then vacuum degassing was performed at 35°C, and then 5000g of the thermal conductive filler prepared in Example 1 was added and stirred continuously; then 50g of hexamethyldisiloxane was added and stirred evenly. Finally, a second vacuum degassing treatment was performed.
[0048] Example 10 15g of calcium carbonate powder with an average particle size of 0.6μm was added to 200g of silica gel and ground and stirred for 2 hours, and then 800g of dimethyl silicone oil and 800g of methyl silicone oil were added and stirred continuously. Then vacuum degassing was performed at 35°C, and then 7000g of the thermal conductive filler prepared in Example 1 was added and stirred continuously; then 50g of tetraethyl silicate was added and stirred evenly. Finally, a second vacuum degassing treatment was performed.
[0049] The thermal conductivity, viscosity and thermal resistance of the silicone grease prepared in Examples 4 to 10 are shown in Table 1. The specific test method is as follows: Thermal conductivity: Under stable conditions, use a thermal conductivity tester to test according to ASTM D5470, Standard Test Method for Heat Transfer of Thermally Conductive Electrical Insulating Materials.
[0050] Viscosity: Use a viscometer to test the viscosity of the sample.
[0051] Table 1 It can be seen from Example 4 and Comparative Example 1 in Table 1 that when the alumina powder is uniformly dispersed in the silicone oil, its viscosity will decrease and the thermal conductivity will increase significantly.
[0052] from Figure 1 It can be seen that in the silicone grease prepared in Example 4, the aluminum oxide powder is dispersed very evenly in the silicone grease. The better the dispersibility of aluminum oxide, the better the performance of the silicone grease and the longer its service life. Figure 2 It can be seen that acenaphthylene oxide pitch has good coating performance on the surface of alumina powder, which shows that acenaphthylene oxide pitch has very good affinity for alumina and silicone oil. Figure 3 It can be seen that when alumina powder is directly added to silicone oil, alumina powder will agglomerate due to its poor dispersibility.
Claims
1. An alumina powder, characterized in that: The surface of the aluminum oxide powder is coated with acenaphthylene oxide pitch.
2. The alumina powder according to claim 1, characterized in that: The D50 of the alumina powder is 5-50 microns.
3. The method for preparing alumina powder according to claim 1, characterized in that: The steps include: After mixing the aluminum oxide powder and acenaphthylene, heating is performed for the first time to polymerize the acenaphthylene, thereby obtaining an aluminum oxide powder with polyacenaphthylene coated on the surface; Plasma treatment is performed on the aluminum oxide powder with polyacenaphthylene coated on the surface to oxidize the polyacenaphthylene, thereby obtaining the aluminum oxide powder with polyacenaphthylene oxide coated on the surface; The aluminum oxide powder coated with oxidized polyacenaphthylene on the surface is heated for the second time to convert the oxidized polyacenaphthylene into acenaphthylene pitch.
4. The method for preparing alumina powder according to claim 3, characterized in that: The mass ratio of the aluminum oxide powder to acenaphthylene is 500-600:
1.
5. The method for preparing alumina powder according to claim 3, characterized in that: The temperature of the first heating is 225-275°C.
6. The method for preparing alumina powder according to claim 3, characterized in that: The plasma treatment time is 5-10min; The gas used in the plasma treatment includes a mixed gas of nitrogen and oxygen or a mixed gas of argon and oxygen; The plasma source power used in the plasma treatment is 400-500W.
7. The method for preparing alumina powder according to claim 3, characterized in that: The temperature of the second heating is 400-500°C.
8. A thermally conductive silicone grease, characterized in that: Comprising the alumina powder as described in claim 1.
9. The thermally conductive silicone grease according to claim 8, characterized in that: The components include 15-20 parts of silicone oil, 50-80 parts of alumina powder and 1-3 parts of silica gel by weight; The silicone oil includes dimethyl silicone oil and / or methyl silicone oil.
10. An application of thermal conductive silicone grease, characterized in that: Used for heat dissipation of electronic components.
Citation Information
Patent Citations
Thermally conductive silicone grease
CN109370227A
Heat-conducting silicone grease as well as preparation method and application of heat-conducting silicone grease
CN116254000A